2014
DOI: 10.1039/c4nr00130c
|View full text |Cite
|
Sign up to set email alerts
|

Mixed solvents for the optimization of morphology in solution-processed, inverted-type perovskite/fullerene hybrid solar cells

Abstract: We investigate mixed solvents of N,N-dimethylformamide (DMF) and γ-butyrolactone (GBL) to produce the smooth surface of a perovskite film and uniform crystal domains. This ideal morphology from mixed solvents enhances the power conversion efficiency to over 6% by improving the exciton dissociation efficiency and reducing the recombination loss at both interfaces of PEDOT:PSS/perovskite and perovskite/PCBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
180
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(191 citation statements)
references
References 27 publications
7
180
3
1
Order By: Relevance
“…In the present study, n = 2 was used for the CH 3 NH 3 PbI 3 because CH 3 NH 3 PbI 3 is a direct transition semiconductor [38]. As shown in Figure 7(b), the E g of the CH 3 NH 3 PbI 3 in the two devices were 1.59 eV, comparable with reported E g of CH 3 NH 3 PbI 3 prepared with a mixed solvent consisting of γ-butyrolactone and DMF [33]. However, there was no peak Figure 2 were used for the energy levels.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…In the present study, n = 2 was used for the CH 3 NH 3 PbI 3 because CH 3 NH 3 PbI 3 is a direct transition semiconductor [38]. As shown in Figure 7(b), the E g of the CH 3 NH 3 PbI 3 in the two devices were 1.59 eV, comparable with reported E g of CH 3 NH 3 PbI 3 prepared with a mixed solvent consisting of γ-butyrolactone and DMF [33]. However, there was no peak Figure 2 were used for the energy levels.…”
Section: Resultssupporting
confidence: 71%
“…Poly(ethylene glycol) (Nacalai Tesque, averaged molecular number: 20,000, 10 mg), acetylacetone (Wako Pure Chemical Industries, 10 μL) and a surfactant (Sigma-Aldrich, Triton X-100, 5 μL) were added in the TiO 2 paste. The paste was stirred for 30 [33]. The molar ratio of the solutes was 1:1.…”
Section: Methodsmentioning
confidence: 99%
“…The thickness of MAPbI 3 Figure 3a shows the XRD patterns of A, B, C, D and E regions of the large-area perovskite MAPbI 3 thin film. It was found that the A, B, C, D and E regions of large-area perovskite MAPbI 3 thin films reveal strong characteristic diffraction peaks of (110), (220) and (330) planes of MAPbI 3 , usually assigned to the tetragonal crystal structure of halide perovskite [22,23]. Also, the MAPbI 3 films in all regions did not have any impurity peak, in which the characteristic peak intensity was high, the crystallinity was high, and the preferred orientation of the film was obvious.…”
Section: Characterizationmentioning
confidence: 99%
“…Various strategies, such as thermal annealing, [13,14] additive inclusion, [15][16][17][18] modification of precursor concentrations and carrier solvents [19,20] and high-temperature-casting [21] have been investigated so far to control perovskite structure, grain size, degree of crystallinity and stability to moisture -however with varying success. [21,22] Here, we introduce the use of commercially available, low molecular-weight organic gelators (LMOGs) LMGOs are commonly used additives in the commodity plastics area because they promotealready at minute quantities -gelation of polymer solutions or melts upon cooling while they have no effect on these systems at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%